A New Mucosal Propeller Flap (Deep Lingual Artery Axial Propeller): The Renaissance of Lingual Flaps. Issue 3 (March 2015) - Cordova, Adriana; Toia, Francesca; D'Arpa, Salvatore; Giunta, Gabriele; Moschella, Francesco
Abstract : Background: Lingual flaps provide ideal mucosal coverage for intraoral defects but traditionally require two surgical stages. The authors present an axial mucosal propeller flap for single-stage intraoral reconstruction. The flap includes the mucosa of the lateral side of the tongue, islanded on the deep lingual vessels. Methods: Between 2011 and 2013, 23 patients underwent intraoral mucosal reconstruction with a deep lingual artery axial propeller flap after cancer resection in the cheek ( n = 16), floor of the mouth ( n = 2), retromolar trigone ( n = 2), hard palate ( n = 2), and soft palate ( n = 1). Mean defect size was 19.5 cm 2 . Preoperative and postoperative intraoral function was evaluated with the Functional Intraoral Glasgow Scale. Results: The authors always achieved one-stage reconstruction with primary donor-site closure. The only complications were an infection treated conservatively and a late oronasal fistula caused by radiotherapy. All patients resumed an oral diet after 1 week and none required surgical revision. Mean 12-month postoperative Functional Intraoral Glasgow Scale score was better than the preoperative score (13.5 versus 12.8). Conclusions: The deep lingual artery axial propeller flap combines the advantages of the traditional lingual flap (i.e., reliable axial vascularization and like-with-like reconstruction) with those of a propeller flap (i.e., one-stage transfer of like tissue and extreme mobility) and has wider indications than a conventional lingual flap. The technique is fast and has low morbidity and good functional results, and the authors recommend it as a first-choice technique to reconstruct moderate to large intraoral defects. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV. Abstract : Supplemental Digital Content is available in the text.